1978
DOI: 10.1111/j.1744-7348.1978.tb02635.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irradiance and water supply on grain development in wheat

Abstract: SUMMARYThe effects of two levels of irradiance and of water supply on grain development in two cultivars of winter wheat were studied by imposing treatments during the phases of cell production and cell expansion in the endosperm. The storage capacity of the grain was determined by cell number in the endosperm, which was reduced by both treatments during the cell production phase. Changes in cell number caused by the treatments were due to changes in the rate of production of cells; the duration of the cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
2
1

Year Published

1981
1981
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 26 publications
4
26
2
1
Order By: Relevance
“…Starch granule number, an indirect measure of the number of amyloplasts in the endosperm, has correlated with final kernel mass in several cereal grain species, including maize (14), wheat (18,19), and barley (5). In the present studies, culturing kernels on medium containing ABA had no apparent effect on the number of starch granules per endosperm during the period of most rapid starch granule initiation (ABA treatment from 11 DAP, Fig.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Starch granule number, an indirect measure of the number of amyloplasts in the endosperm, has correlated with final kernel mass in several cereal grain species, including maize (14), wheat (18,19), and barley (5). In the present studies, culturing kernels on medium containing ABA had no apparent effect on the number of starch granules per endosperm during the period of most rapid starch granule initiation (ABA treatment from 11 DAP, Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Decreases in final kernel mass in response to environmental stresses have correlated well with decreases in endosperm cell number in maize (14), as well as in other cereal grain species (5,18,19). Perhaps in the present case also, the ABA-induced decrease in endosperm cell number limited the maximal storage capacity of the kernel, and in tum, decreased the mature dry mass (Table II), even though fresh weight growth and starch granule initiation were relatively unaffected.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…FRIEND (1965) (1970). BROCKLEHURST et al (1978) found that reduced irradiance during the cell production phase decreased grain weight by 13 07o when sampled 14 days after anthesis, while in our results grain weight was only reduced 5.3 %, a non-significant change (table 4) …”
contrasting
confidence: 49%